Pharmacological Treatment of Herpes Zoster and Factors Associated with Its Recurrence - Luis Fernando Valladales-Restrepo; Santiago Velasquez-Quimara; Jorge Enrique Machado-Alba (Antibiotics, 2023)
The burden of herpes zoster disease is significant worldwide, with millions affected and an increasing incidence. Increased age and immunosuppression due to disease or drugs have been related to its recurrence. The aim of this work was to determine the pharmacological management of herpes zoster and identify factors associated with recurrence, representing a longitudinal retrospective study identifying the pharmacological management of patients with herpes zoster and the factors related to the first recurrence using a population database. Follow-up was carried out for up to 2 years, and descriptive analysis and Cox proportional hazards regression were performed. A total of 2978 patients with herpes zoster were identified, with a median age of 58.9 years and 65.2% being women. The treatment mainly involved acyclovir (98.3%), acetaminophen (36.0%), and non-steroidal anti-inflammatory drugs (33.9%). A total of 2.3% of patients had a first recurrence. Corticosteroids were used in a greater proportion for recurrence than for the initial herpes episode (18.8% vs. 9.8%, respectively). Being female (HR:2.68;95%CI:1.39–5.17), age ≥60 years (HR:1.74;95%CI:1.02–2.96), having liver cirrhosis (HR:7.10;95%CI:1.69–29.80), and having hypothyroidism (HR:1.99;95%CI:1.16–3.40) were associated with greater probability of a first recurrence. The vast majority of patients were managed with acyclovir, and the use of acetaminophen or non-steroidal anti-inflammatory drugs for pain management was frequent. Several conditions were found that increased the probability of presenting a first recurrence of herpes zoster, such as age over 60 years, being a woman, suffering from hypothyroidism, and liver cirrhosis.